Prevalencia y factores asociados al VIH en habitante de calle de la ciudad de Medellín Colombia (2015)
ABSTRACT: To determine the prevalence of HIV and describe the social and demographic characteristics of street dwellers Medellin in 2014. Methodology: A descriptive cross-sectional study where the authors determined the seroprevalence of HIV and explored the social and demographic factors associated with HIV infection among street dwellers of the city of Medellin in 2014. The data were processed using the SPSS 21.0 software. Analyses included univariate and bivariate descriptions, and the statistical Chi-square test was used. Prevalence ratio (PR) confidence interval 95% assuming a statistical significance level of less than 5%. Results: a total of 184 street dwellers were surveyed, 80% were male, with an average age of 40 (SD 11.4 years). An HIV prevalence of 8.2% was found; for men, this prevalence was 6.1% and for women 16.2%. Women had three times the risk of HIV compared to men; those who were cohabiting and married had five times the risk of having HIV compared to single, separated and divorced individuals. Conclusion:The higher prevalence amounting to 5% for the street dwellers shows that HIV infection in Colombia is concentrated in key groups (i.e. those having high prevalence and vulnerability) requiring actions focusing on specific of groups.